Potential spread and economic impact of invasive Drosophila suzukii in Brazil - Benito, Norton Polo; Lopes-da-Silva, Marcelo; Santos, Régis Sivori Silva dos (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to outline the potential distribution and economic impact of Drosophila suzukii (Diptera: Drosophilidae), a recent invasive pest, in Brazil. Two maps of the potential establishment of the species were drawn based on the ecoclimatic index (EI), which uses the following thermal requirements for the species: with thermal stress, most restrictive scenario for spread; and without thermal stress. The EI was classified into four ranges: unfavorable, ≤25%; less favorable, >25 to ≤50%; favorable, >50 to ≤75%; and highly favorable, >75%. Economic losses were estimated based on the most restrictive map. The highly favorable areas were overlapped with those of the maps of production data for each possible host (apple, grape, peach, persimmon, fig, and pear). Considering these six hosts, the overlap between the highly favorable and the production areas varied from 45.5% (grape) to 98.3% (apple). However, the monetary estimation of the potential losses in the worst case scenario (no control measures) was possible only for figs and peaches. Southern Brazil is the most climatically favorable area for D. suzukii development and where potential economic losses are expected to be the greatest. Maximum average temperatures (>30°C) are the main ecological factor to limit D. suzukii spread in Brazil.